The forensic analysis of office paper using oxygen isotope ratio mass spectrometry. Part 1: Understanding the background population and homogeneity of paper for the comparison and discrimination of samples. (May 2016) - Jones, Kylie; Benson, Sarah; Roux, Claude
Highlights: IRMS was used to compare 123 office papers using oxygen isotopic abundance values. Inter and intra sample variability was determined to inform discrimination. 82% of the 123 papers were different using a discrimination factor of 0.7 ‰. Combination with carbon isotopes and other examinations to be explored in future. Abstract: Isotope ratio mass spectrometry (IRMS) using carbon isotopes has previously been shown to be a robust and discriminating technique for the comparison of document papers. This study aims to examine the inter and intra sample variability for oxygen isotopes measured in standard 80gsm white document papers, to inform the comparison of document papers in forensic casework. 123 paper samples collected from Australia and New Zealand over a 24-month period were measured for their bulk oxygen isotopic abundance and were found to sit within a range of 15 ‰. A homogeneity study was undertaken which included examining the variability of samples at the sheet, ream and brand source levels. The results of this study were used to construct guidelines for sample comparison and as such, 95% confidence intervals were observed to be inappropriate for use given the high intra sample variability. Instead, a 1.4 ‰ discrimination range (0.7 ‰ either side of the measured value) was defined for use as a benchmark for discrimination when samples were measured in the same sequence. Utilising this value, 82% of the samples could be discriminated using a paired comparison, demonstrating a strong potential for use within forensic casework.